Adobe Soundbooth CS3 - Smith, Steven; Virtual Training Company ([Australia] : Virtual Training Company, 2008)
This course provides students with a thorough knowledge of Soundbooth's interface, components and capabilities. Soundbooth's included browser (Adobe Bridge) is also covered in great detail with a specific focus on its integration into the soundbooth workflow
Title from container
Training CD
Contains 84 movies with total time 7.5 hours
See record from bib id 3424179 for payment details
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: Digital audio editors